PENGEMBANGAN LKS PRAKTIKUM BERBASIS KIT FISIKA UNTUK KELAS X SMA/MA - Yenti, Welna Risna; Lizelwati, Novia; Mahrizal, Mahrizal (Jurnal Pembelajaran MIPA, 2014)
The aim of this research was to produce a kit-based physics lab worksheets for class X SMA/MA which valid and practical. Kind of research is the research and development refers to research and development 4-D model. Research procedures can divided into three steps, that are namely define, design and development. The research instrument used was a validation sheet, observation sheets, and questionnaire responses sheets.The research instrument developed by arranging the item of instrument, doing the validity test, and analysis of praktikalisasi results. The results showed that: 1). kit-based physics lab worksheets are very valid based on the percentage of 92% 2). Use of kit-based physics lab worksheets in teaching do not significant barriers experience, according to its used by observer sense practical and student assessment.Key words: development, lab worksheets, high school physics kits, validation, praktikalisasi